A Review on the Role of Pilocarpine on the Management of Xerostomia and the Importance of the Topical Administration Systems Development - Afroditi Kapourani; Konstantinos N. Kontogiannopoulos; Panagiotis Barmpalexis (Pharmaceuticals, 2022)
Xerostomia is linked to an increased risk of dental caries, oral fungal infections, and speaking/swallowing difficulties, factors that may significantly degrade patients’ life, socially- or emotionally-wise. Consequently, there is an increasing interest in developing management approaches for confronting this oral condition, at which pilocarpine, a parasympathomimetic agent, plays a vital role. Although the therapeutic effects of orally administrated pilocarpine on the salivary gland flow and the symptoms of xerostomia have been proved by numerous studies, the systemic administration of this drug is affiliated with various adverse effects. Some of the typical adverse effects include sweating, nausea, vomiting, diarrhea, rhinitis, dizziness and increased urinary frequency. In this vein, new strategies to develop novel and effective dosage forms for topical (i.e., in the oral cavity) pilocarpine administration, in order for the salivary flow to be enhanced with minimal systemic manifestations, have emerged. Therefore, the purpose of the current review is to survey the literature concerning the performance of topical pilocarpine delivery systems. According to the findings, the topical delivery of pilocarpine can be regarded as the equivalent to systemic delivery of the drug, efficacy-wise, but with improved patient tolerance and less adverse effects.